2020
DOI: 10.1073/pnas.2001123117
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in undoped BaFe 2 As 2 by tetrahedral geometry design

Abstract: Fe-based superconductors exhibit a diverse interplay between charge, orbital, and magnetic ordering. Variations in atomic geometry affect electron hopping between Fe atoms and the Fermi surface topology, influencing magnetic frustration and the pairing strength through changes of orbital overlap and occupancies. Here, we experimentally demonstrate a systematic approach to realize superconductivity without chemical doping in BaFe2As2, employing geometric design within an epitaxial heterostructure. We control bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…The addition of a chemical dopant and/or the application of pressure on BaFe 2 As 2 results in the eradication of the SDW and, therefore, in the reduction of magnetic order. Superconductivity is observed when the magnetic order is sufficiently weak; thus, superconductivity and weak magnetic order can still coexist [37,38,40]. The exact mechanism for the emergence of superconductivity is, however, still unknown.…”
Section: Mathematical Formulation Of the Problemmentioning
confidence: 99%
“…The addition of a chemical dopant and/or the application of pressure on BaFe 2 As 2 results in the eradication of the SDW and, therefore, in the reduction of magnetic order. Superconductivity is observed when the magnetic order is sufficiently weak; thus, superconductivity and weak magnetic order can still coexist [37,38,40]. The exact mechanism for the emergence of superconductivity is, however, still unknown.…”
Section: Mathematical Formulation Of the Problemmentioning
confidence: 99%
“…Previous studies have shown that the superconductivities of Ba122 superconductors are affected by various factors. A number of experiments found that the superconducting T c 's are influenced by the geometrical structures [29][30][31], such as the As height with respect to the Fe-Fe plane [32,33] and the Fe-As-Fe angles [34][35][36]. It has also been reported that the magnetism plays a vital role in the superconductivity of Ba122 system [4,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Superconductivity arises from suppressing the magnetic order and structural phase transition upon doping with electrons or holes. [10] More recently, superconductivity is induced in BaFe 2 As 2 compound without doping or even applying hydrostatic pressure, [11] providing a deeper insight into the interplay between magnetic/structural and superconducting transition. It is clear that magnetic order and superconducting transition are mutually exclusive, however charge nematicity, SDW and structural transition emerge in almost the same region of the phase diagram, resulting in the ambiguity of these orders at transition points.…”
Section: Introductionmentioning
confidence: 99%